A Universidade Federal de Mato Grosso no ciclo contemporâneo de reformas da educação superior brasileira : dinâmica e alterações - Gomes, Crisanvania Luiz (2015)
This study was developed since an analytical framework about the changes in the Brazilian higher education field, from the 2000s, being conventionally called expansionary policies. In this research, all the effort here undertaken, had support in a critical perspective, taken as study object the inclusion of Mato Grosso Federal University under the expansionary policies in their most recent cycle, in order to present and analyze the changes in its dynamics from this insertion, specially about the dimensions of the entree (entree seats, entree, selective format) and permanence (registration permanence, graduation rates, student attachment programs). To start, the approach to the theme demanded an immersion in the professional literature in order to give more density to the analysis, that also allows a better design of the study object. Another methodological procedure that surrounded the realization of this qualitative study, based on quantitative data, involved in addition to the literature, the use of documentary sources. This study intented understand the following question: the most recent expansionary measures adopted by UFMT have caused the much-touted significant loss of its student group? It deserves careful analysis of the results given the complexity surrounding the entry process and student permancence in a higher education institution on which can not be refered a single factor that changes its dynamics.